LEARNING ENGLISH BY USING WHATSAPP APPLICATIONS DUE TO COVID-19 - Pingkan Indah Mahayati; Lulud Oktaviani (Faculty of Arts and Education, 2022)
Online learning activities are implemented simultaneously in Indonesia due to the spread of the coronavirus, Coronavirus disease or covid-19 is spared very fast, speeding to almost all countries. With the implementation of online learning, this research discusses English learning activities using the Whatsapp application as a medium. This study uses a qualitative method to collect data through interviews with various students participating in e-learning. According to the interview results, students are satisfied with e-learning because teachers are more creative in dealing with several media. These tools will particularly motivate students to learn English. Using the Whatsapp Application allows students to freely consult the materials provided by the teacher, discuss with other students, watch videos or view various documents related to the materials. although there are some obstacles in using the internet, such as the connection is not good enough. Students still enjoy E-learning because they use methods that are not boring.